Determinasi Kemampuan Auditor Dalam Mendeteksi Kecurangan - Rudi Syaf Putra; Armel, R. Septian (LPPM Universitas Pelita Bangsa, 2025)
The rapid advancement of technology has provided various conveniences for humanity. However, these conveniences have also prompted some individuals to engage in fraudulent activities for personal or group gain. Therefore, fraud detection by auditors is crucial to prevent such misconduct. This study employs a quantitative approach to analyze the partial effects of professional skepticism, independence, auditor experience, competence, and audit training on auditors' ability to detect fraud. The sample for this research consists of 76 auditors, selected using a Non-Probability Sampling technique. Data were collected through the distribution of questionnaires directly to auditors at the Representative Office of BPKP in Riau Province. Data analysis was conducted using validity and reliability tests, classical assumption tests, linear regression tests, and t-tests. The data processing was performed using SPSS. The results indicate that auditor experience and audit training do not significantly influence auditors' ability, while competence significantly impacts auditors' ability to detect fraud